PATOGENICIDAD DE HONGOS AISLADOS DEL ALCORNOQUE EN CATALUÑA - LUQUE, J; ÁLVAREZ, I (II Congreso Forestal Español, 1997)
Forty four fungal strains were used in pathogenicity tests made in trunk (32), leaves (8), and roots (8) of cork oak plants (Quereus suber L.) with two irrigation treatments (adequate and stress). Eleven species were found to be pathogenic on tnmk and three on leaf. Trunk pathogens such as Botryosphaeria stevensii, Phytophthora einnamomi, and (?)Diseula sp. caused the death of the inoculated plants. Hydric stress increased both canker and necrosis formation by (?)Diseula sp. and H. mediterraneum, reduced the effects of P. cinnamomi and had no effect on B. stevensii. The latter fungus was a virulent pathogen irrespectively of the irrigation treatment. Dendrophoma myriadea and (?)Fusieoeeum sp. were pathogenic on leaves. Both fungi were negatively affected by the hydric stress. However, no satisfactory results were obtained in the root inoculations. K.W.:
Keywords: Botryosphaeria stevensii; decline; Hypoxylon mediterraneum; pathogenic fungi; phytophthora cinnamomi; Quercus suber